Effects of Brief Behavioral Treatment for Insomnia on Daily Associations between Self-Reported Sleep and Objective Cognitive Performance in Older Adults. Issue 5 (2nd September 2020) - McCrae, Christina S.; Curtis, Ashley F.; Williams, Jacob M.; Dautovich, Natalie D.; McNamara, Joseph P. H.; Stripling, Ashley; Dzierzewski, Joseph M.; Berry, Richard B.; McCoy, Karin M.; Marsiske, Michael
ABSTRACT: Objective: Behavioral treatments for insomnia improve sleep in older adults, but research documenting their effects on cognitive performance is mixed. We explored whether a brief behavioral treatment for insomnia (BBTi) impacts daily associations between sleep parameters and next day cognition. Methods: Sixty-two older adults ( Mage = 69.45 years, SD = 7.71) with insomnia completed either 4 weeks of BBTi or self-monitoring control (SMC). At baseline, post-treatment, and 3 month follow-up, participants completed 14 days of diaries measuring sleep onset latency (SOL), wake after sleep onset (WASO), total sleep time (TST), and sleep efficiency (SE), as well as daily cognitive tests measuring processing speed (i.e., symbol digit modalities test, SDMT), and reasoning (i.e., letter series). At each time period, associations between sleep parameters and daily cognition, controlling for age, education, insomnia duration, use of sleep medications, and depression (i.e., Beck Depression Inventory–2 nd Edition scores), were examined through multilevel modeling. Results: At post-treatment, we observed an interactive fixed effect of treatment condition (i.e., BBTi/SMC) and TST on daily SDMT and letter series performance. For BBTi, longer TST was associated with better letter series performance, and did not predict SDMT performance. For SMC, longer TST was associated with worse SDMT, and was not associated with letter series performance. Greater WASO (regardless of group) was associated with better SDMT performance at post-treatment. Associations were not maintained at follow-up. Conclusions: Sleep duration may play an important role in BBTi-related improvements in daily higher order cognition. Maintenance of these associations may be facilitated by booster sessions following post-treatment. Clinical Trial Identifier: NCT02967185